Presidential Studies sebagai Paradigma Baru dalam Pendidikan Politik di Indonesia: Sebuah Kajian Konseptual - Rohman Rohman; Lalu Rohadi Rahman; Antonius Sukoco (CV. Global Cendekia Inti, 2026)
This article aims to formulate Presidential Studies as a new paradigm in political education in Indonesia. The study employs a conceptual approach based on a comprehensive literature review of theories of presidentialism, the dynamics of Indonesian democracy, and civic education. The findings indicate that political education in Indonesia remains predominantly normative-institutional and has not yet comprehensively integrated presidential studies. In a multiparty presidential system such as Indonesia, the relationships among the president, political parties, bureaucracy, and civil society play a decisive role in determining the quality of democracy. Presidential Studies offers an integrative framework that connects theories of executive power, political leadership, party institutionalization, and deliberative democratic pedagogy. This paradigm contributes to strengthening critical political literacy, preventing identity politics, and fostering democratic participation grounded in Pancasila values.